Rotaxanes comprising cyclic phenylenedioxydiacetamides and secondary mono- and bis-dialkylammonium ions: effect of macrocyclic ring size on pseudorotaxane formation. Issue 3 (3rd January 2020) - Nakamura, Takanori; Mori, Yuka; Naito, Masaya; Okuma, Yukari; Miyagawa, Shinobu; Takaya, Hikaru; Kawasaki, Tsuneomi; Tokunaga, Yuji
Abstract : [2]Rotaxanes, stabilized through multiple and cooperative hydrogen bonding system, were synthesized from dialkylammonium ions and macrocycle possessing two phenylenedioxydiacetamide units and appropriate spacers. Abstract : In this study we synthesized three macrocyclic tetralactams 1, possessing two phenylenedioxydiacetamide units and various spacers, for use as hydrogen bond accepting hosts for mono- and bis-dialkylammonium ions. The cyclic tetralactam 1b, featuring propylene spacers, bound secondary mono- and bis-dialkylammonium ions efficiently to form corresponding pseudo[2]rotaxanes stabilized through hydrogen bonding between the two components. The cyclic tetralactams bearing other spacers (1a and 1d ) also bound these dialkylammonium ions, but the macrocycle 1a (ethylene spacer) predominantly constructed a face-to-face complex, while the macrocycle 1d (3-oxypentalene spacer) formed a non-selective complex. We synthesized three [2]rotaxanes, through imine and oxime formation, from pseudo[2]rotaxanes self-assembled from the propylene-spacer tetralactam 1b and mono- and bis-alkylammonium ions. 1 H NMR spectroscopy and X-ray crystallography revealed that hydrogen bonds between the dumbbell-shaped and macrocyclic components restricted the conformation of the amide units in the [2]rotaxanes in solution and in the solid state.